2022
DOI: 10.1002/advs.202203759
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines Promote Aragonite Nucleation and Generate Biomimetic Structures

Abstract: Calcium carbonate biomineralization is remarkable for the ability of organisms to produce calcite or aragonite with perfect fidelity, where this is commonly attributed to specific anionic biomacromolecules. However, it is proven difficult to mimic this behavior using synthetic or biogenic anionic organic molecules. Here, it is shown that cationic polyamines ranging from small molecules to large polyelectrolytes can exert exceptional control over calcium carbonate polymorph, promoting aragonite nucleation at ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…5 and 6) imply that the spindles formed by particle attachment, i.e., in a non-classical crystallization process, as was also suggested by previous authors. 6,12,15,26,35 The formation of mesocrystals via the attachment of crystalline nanoparticles in a crystallographically co-aligned fashion was widely described, e.g., in titanium oxides, 32,48 iron oxides, 34,49,50 and calcium sulphates. 51,51,52 However, the rapid oriented attachment of aragonite nanocrystals is unlikely after their burst nucleation at room temperature, in a weak electrolyte solution, at slightly alkaline pH; moreover, we never observed individual aragonite nanocrystals in our samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 and 6) imply that the spindles formed by particle attachment, i.e., in a non-classical crystallization process, as was also suggested by previous authors. 6,12,15,26,35 The formation of mesocrystals via the attachment of crystalline nanoparticles in a crystallographically co-aligned fashion was widely described, e.g., in titanium oxides, 32,48 iron oxides, 34,49,50 and calcium sulphates. 51,51,52 However, the rapid oriented attachment of aragonite nanocrystals is unlikely after their burst nucleation at room temperature, in a weak electrolyte solution, at slightly alkaline pH; moreover, we never observed individual aragonite nanocrystals in our samples.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] These properties have been observed in both natural 13 and synthetic samples, the latter including both abiotically 6,9,11,[14][15][16][17][18][19][20][21][22][23] and biomimetically synthesized aragonite. 12,[24][25][26][27] Whether they formed homogeneously 10 or in the presence of additives (such as polyaspartic and amino acids, 28 solely amino acids, 26 polyamides, 12 or swelling clay minerals 11 ), the mesocrystalline characters of aragonite aggregates were similar. Despite their widespread occurrence, the formation mechanism of aragonite spindles is not clearly understood, even though such an understanding could shed light on important aspects of the formation of mesocrystals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mollusk shells are predominantly composed of CaCO 3 . In recent years, the in vitro biomimetic mineralization process of calcium carbonate has received great attention from researchers. Studies have shown that silk proteins can also influence the morphology of CaCO 3 crystals. Cheng et al utilized recombinant SF (RSF) as a template to produce a hollow rice-like CaCO 3 /RSF hybrid.…”
Section: Biominerals Induced By Silk Protein Templatesmentioning
confidence: 99%
“…aminefunctionalized) polymer additives and their role is increasingly being recognized. [38][39][40] In bioinspired polymer-mediated mineralization, synthetic polyelectrolytes have been shown to exert multiple effects. Examples include the stabilization of transient amorphous precursors of hydrated colloids even in the presence of minute amounts of organic molecules, 41 promotion of the formation and stabilization of an amorphous precursor phase by suppressing crystalline growth, 42 altering the pH value of the reaction solution, 41 or affecting the composition and water content of the mineral phase, resulting in a manifold of different crystal morphologies.…”
Section: Introductionmentioning
confidence: 99%